ANALISIS PENERAPAN PP 46 TAHUN 2013 BAGI UMKM DALAM MEMPERTAHANKAN KEBERADAAN UMKM DI INDONESIA - Tri Anita (Universitas Indraprasta PGRI, 2015)
Developing Micro, Small to Medium Enterprises (SMEs) in Indonesia make this sector as a potential sector to be continuously developed by the government. It is proven that sector have great contribute for the growth Indonesian economic. According to magsiltude potential of sector that, the government implemented tax policy for SMEs in PP 46 2013. This research is a review of the literature which impact of policy on the application of PP 46 of 2013 for the survival of SMEs in Indonesia. This research have expected contribution for next research about the implementation of PP 46 for SMEs in Indonesia. Keywords : Application, Tax, and SMEs